Medicine ball throw responsiveness to measure wheelchair basketball mobility in male players - Rodrigues Gomes Costa, R.; Rodrigues Dorneles, J.; Lopes, G. H.; Gorla, J. I.; Ribeiro Neto, F. (Journal of Sport Rehabilitation, 2021)
Cntext: Monitoring training loads and consequent fatigue responses are usually a result of personal trainers` experiences and and adaptation of methods used in sports for people without disabilities. Currently, there is little scientific evidence on the relationship between training load and fatigue resulting from training sessions in wheelchair sports. Analogous to the vertical jump, which has been associated with competitive performance and used to assess fatigue in Olympic sports, the medicine ball throw (MBT) is a fast, feasible, and accessible test that might be used to measure performance outcomes in Paralympic athletes. Objective: To test the MBT responsiveness to detect meaningful changes after training sessions in beginner wheelchair basketball players (WBP). Design: Cross-sectional study. Setting: Rehabilitation Hospital Network, Paralympic Program. Participants: Twelve male WBP. Main Outcomes Measures: The participants performed 3 consecutive days of training sessions involving exercises of wheelchair basketball skills, strength, and power. The MBT test was performed pre and post training sessions. Results: The smallest worthwhile change for MBT was 0.10 cm, and the lower and upper limits were 3.54 and 3.75 m, respectively. On the first day, the MBT started below the smallest worthwhile change lower limit and increased above the upper limit (3.53 and 3.78 m, respectively). On the second day, the MBT pretraining and posttraining session results were near the sample mean (3.62 and 3.59 m, respectively). On the third day, the WBP started the MBT test training higher than the upper limit (3.78 m) and decreased to near the mean (3.58 m). Conclusions: During 3 consecutive days of training sessions, the magnitude based inference model presented meaningful changes in MBT test performance. The accurate association of the magnitude-based inference model with the MBT allows coaches and sports team staff to interpret the correct magnitude of change in WBP performance